ANALISIS NERACA AIR DI KABUPATEN MALUKU TENGGARA PROVINSI MALUKU - Kamila Fadyana Putri; Haryono Putro (Institut Teknologi Bandung, 2020)
AbstractWater Balance is the information of research that explains balancing of potential, supply and demand of water in a certain period of time, and it can be seen wether demand and supply of water have been balanced, so that it can be taken as a decision making for water infrastructure planning. Water potential in Southeast Maluku Regency with Penman Modification and F.J.Mock method has a total monthly dependable flow in 1 year 596,015.m3/second. The availability of water was obtained by the total water resources infrastructure 0,647.m3/second. Water demand were calculated for all sectors in the study location, such as; industrial-urban households (RKI), agriculture and plantations, and livestock with exponential method, with total debit 4,822.m3/second for projections up to 2039. The agriculture and plantation sectors are the most dominant sectors which needs water, with 45,11% projected percentage up to 2039. Water balance analysis concludes that water potential in Southeast Maluku Regency can still fulfill the demand of water until 2039, but there is a gap between the water demand and the availability of existing water resources infrastructure. Water demand in 2017 with total debit 0,836 m3/detik has not fulfilled by total water supply 0,647.m3/second.AbstrakNeraca air adalah informasi hasil penelitian berisi imbangan potensi, ketersediaan dan kebutuhan sumber daya air pada kurun waktu tertentu, nantinya dapat dilihat apakah kebutuhan dan ketersediaan air sudah seimbang, sehingga bisa dijadikan pertimbangan untuk tahap perencanaan infrastruktur keairan selanjutnya. Potensi air di Kabupaten Maluku Tenggara dengan metode Penman Modifikasi dan F.J.Mock didapatkan total debit andalan bulanan dalam 1 tahun sebesar 596,015.m3/detik. Ketersediaan air didapatkan total debit infrastruktur SDA sebesar 0,647.m3/detik. Kebutuhan air diperhitungkan untuk semua sektor yang ada di lokasi studi, seperti; rumah tangga-kota-industri (RKI), pertanian dan perkebunan, serta peternakan menggunakan metode eksponensial dengan total debit 4,822.m3/detik untuk proyeksi hingga tahun 2039. Sektor pertanian dan perkebunan menjadi sektor yang paling dominan membutuhkan air, dengan presentase proyeksi hingga tahun 2039 sebesar 45,11%. Analisis neraca air diperoleh kesimpulan potensi air di Kabupaten Maluku Tenggara masih dapat memenuhi kebutuhan air hingga tahun 2039, tetapi terjadi kesenjangan antara kebutuhan air dengan ketersediaan infrastruktur SDA yang ada. Kebutuhan air di tahun 2017 sebesar 0,836.m3/detik belum terpenuhi oleh ketersediaan air yang ada sebesar 0,647 m3/detik.